« Base Phrygian Turk! » Injures et « espèces de… » : analyse microscopique d’un étrange spécimen shakespearien - Nathalie Vienne-Guerrin (Revue LISA)
This article offers an interpretation of the strange term “base Phrygian Turk” that Pistol uses to insult Falstaff in The Merry Wives of Windsor. If the spectators understand why Slender is called “latten bilbo” (1.1.150) or “Banbury Cheese” (2.2.120), and why Falstaff is called “whale” (2.1.56), “hodge pudding” (5.5.150) or “bag of flax” (5.5.150), this “Base Phrygian Turk” is less transparent and resists interpretation. Using Evelyne Larguèche’s theoretical work on the insulting effect (“l’effet injure”), we ask the question whether there is meaning behind these abusive words or whether their meaning only resides in the speech-act that consists in insulting. Studying the representation of the Islamic world in Elizabethan society and theatre, we show that far from being a mere “pistolism”, this insult suggests that Falstaff “turns Turk” in this play.